Construction of a SNP-Based Genetic Map Using SLAF-Seq and QTL Analysis of Morphological Traits in Eggplant - Wei, Qingzhen; Wang, Wuhong; Hu, Tianhua; Hu, Haijiao; Wang, Jinglei; Bao, Chonglai (Frontiers in Genetics, 2020)
Eggplant (Solanum melongena；2n=24) is an economically important fruit crop of the family Solanaceae that was domesticated in India and Southeast Asia. Construction of a high-resolution genetic map and map-based gene mining in eggplant have lagged behind other crops within the family such as tomato and potato. In this study, we conducted high-throughput single nucleotide polymorphism (SNP) discovery in the eggplant genome using specific length amplified fragment (SLAF) sequencing, and constructed a high-density genetic map for the quantitative trait locus (QTL) analysis of multiple traits. An inter-specific F2 population of 121 individuals was developed from the cross between cultivated eggplant “1836” and the wild relative S. linnaeanum ”1809”. Genomic DNA extracted from parental lines and the F2 population was subjected to high-throughput SLAF sequencing. A total of 111.74 Gb data and 487.53 million pair-end reads were generated. A high-resolution genetic map containing 2,122 SNP markers and 12 linkage groups was developed for eggplant, which spanned 1530.75 cM with an average distance of 0.72 cM between adjacent markers. A total of 19 QTLs were detected for stem height, and fruit and leaf morphology traits of eggplant, explaining 4.08–55.23% of the phenotypic variance. These QTLs were distributed on nine linkage groups (LGs), but not on LG2, 4, and 9. The number of SNPs ranged from 2 to 11 within each QTL, and the genetic interval varied from 0.15 to 10.53 cM. Overall, the results establish a foundation for the fine mapping of complex QTLs, candidate gene identification, and marker-assisted selection of favorable alleles in eggplant breeding.